Hybrid Tree Harvester Machine with Battery Powered Hydro-Electric Drive. (18th November 2019) - Prochazka, Petr; Pazdera, Ivo; Cipin, Radoslav
Abstract : The paper describe design of battery powered drive unit intended for tree harvester application. Battery powered hybrid drive unit in working machine is currently quite common (1). The battery capacitance is not sufficient to realize harvester as an only battery powered machine. Nevertheless, the hybrid concept of electric drive is useful to cover short power peaks demands during the harvester standard operation. In harvester application there is typical high ratio between short power peak and average demanded power. The development in batteries increases of significance and possibility of electric drive utilization in three harvesters.